Terrestrial isopods (Isopoda, Crustacea) from the “Danube Delta” Biosphere Reserve - Nicolae TOMESCU; Lucian Alexandru TEODOR (Studia Universitatis Babeș-Bolyai. Biologia, 2018)
The authors describe the fauna of terrestrial isopods and the habitats analysed in 13 sites located in the Biosphere Reserve “Danube Delta”: Letea Forest, Periprava Village, the Levees Maliuc, Caraorman, Dunavăţ, Sfântu Gheorghe, Sacalin Island, Popina Island, Enisala Fortress, Sălcioara (6 Martie) Forest, Doloşman Hill, Gura Portiţei and Lupilor Levee. In the investigated habitats 14 species of terrestrial isopods were identified: Hyloniscus riparius, Haplophtalmus orientalis, Cylisticus convexus, Porcellionides (= Metoponorthus) pruinosus, Orthometopon romanicus n. sp., Protracheoniscus politus, Porcellium collicola, Trachelipus arcuatus, Trachelipus nodulosus, Trachelipus rathkii, Trachelipus ratzeburgi, Trachelipus squamuliger, Armadillidium vulgare, Armadillidium jaqueti.